Antecedents of electronic wallet adoption: a unified adoption based perspective on a demonetised economy. (5th July 2019) - Sikdar, Pallab; Kumar, Amresh; Alam, Md. Moddassir
Electronic wallet has been a disruptive innovation in payments landscape. It has afforded convenience from remitters' perspective and transactional efficiency to the beneficiary. The gradually increasing significance of e-wallets warrants an exploration of antecedents leading to adoption of electronic wallets by the users. Digitising the payments assume enhanced importance in an economy where level of disposable household currency is reduced owing to sovereign policies. Present study employs UTAUT2 framework towards investigating the factors generating usage intentions for electronic wallet applications and the extent to which such intentions translate to final usage behaviour. Demonetised Indian economy constitutes the geographical base for the study, while respondents comprise of individuals possessing awareness and prior experience of electronic wallet usage. Structural equation modelling was applied to primary data gathered from 462 respondents. Findings reveal positive significant intention-based causations arising from five out the seven conceptualised constructs in a demonetised economic environment, while usage intentions were found to be significantly and positively translating to usage behaviour.